2006
DOI: 10.1136/bjo.2006.105338
|View full text |Cite
|
Sign up to set email alerts
|

Value of retinal vein pulsation characteristics in predicting increased optic disc excavation

Abstract: Background: Retinal vein pulsation is often absent in glaucoma, but can be induced by applying a graded ophthalmodynamometric force (ODF) to the eye, which is elevated in glaucoma. Aim: To assess whether ODF has a predictive value in determining glaucoma progression. Methods: 75 patients with glaucoma and suspected glaucoma were examined prospectively in 1996, and then re-examined at a mean of 82 months later. All subjects had intraocular pressure, visual fields, stereo optic disc photography and ODF measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 26 publications
3
54
0
3
Order By: Relevance
“…Our finding is in line with the results of a previous investigation by Balaratnasingam et al, 27 who examined the influence of the ophthalmodynamometric force (ODF) to the future optic disc excavation. ODF was compared in patients with and without DH as a subgroup analysis and no significant difference between the DH group and non-DH group was found.…”
Section: Discussionsupporting
confidence: 82%
“…Our finding is in line with the results of a previous investigation by Balaratnasingam et al, 27 who examined the influence of the ophthalmodynamometric force (ODF) to the future optic disc excavation. ODF was compared in patients with and without DH as a subgroup analysis and no significant difference between the DH group and non-DH group was found.…”
Section: Discussionsupporting
confidence: 82%
“…7 Various associations have also been reported between SVP and glaucoma: (1) venous pulsation evoked by ophthalmodynamometry indicates higher venous pressure in glaucoma subjects, [8][9][10] (2) SVP incidence is lower in glaucoma, [11][12][13][14] (3) SVP is related to the severity of functional damage, 11,13,15,16 and (4) SVP is predictive of disease progression. [17][18][19] Obviously, SVP could be employed more efficiently if its etiology was better understood.…”
Section: Introductionmentioning
confidence: 99%
“…The study may add to the clinical application of modern ophthalmodynamometry as already demonstrated in previous investigations on glaucoma, measurement of intracerebral pressure, assessment of tissue pressure in the orbit in patients with endocrine orbitopathy, ischaemic ophthalmopathy and retinal vein occlusions. [4][5][6][7][8][9][10][11][12] …”
Section: Resultsmentioning
confidence: 99%